A Destination Specific Analysis of Tourism Infrastructure in Kashmir Valley in the Course of Application of Composite Index Methodology - GOWHAR AHMAD WANI (ASEAN Journal on Hospitality and Tourism, 2023)
The paper is empirical in the course of methodological contributions and policy implications. It studies the quantity of tourism infrastructure obtainable for destinations in the Kashmir Valley. For analysis, quantitative data were collected from the head offices of numerous departments facilitating infrastructure facilities. The Union Territory of Jammu and Kashmir is widely famous for its tourism potentials. Nevertheless, it needs to catch up in tourism infrastructure. The low quantity is visible in components and needs a comprehensive measurement to identify lags. Subsequently, identifying the significant areas of weakness required a scientific mechanism and an approach to remove such bottlenecks. Therefore, measurement of Infrastructure based on scientific methods is indispensable to identify the areas of inadequate facilities and to remove obstructions. Subsequently, composite index based analyses were adopted to compare and rank the quantity of Infrastructure of five popular tourism destinations. Tourism Infrastructure Index exposed disparity by dimensions and among the destinations. It is revealed that a low amount of Infrastructure is evident for most destinations and, therefore, affects the development of tourist places. So, the provision of sufficient quantity is recommended and depends upon the geospatial characteristics, nature and necessities of the destinations.